Efforts To Increase Professionality Of Teacher Of Beginning Of Elementary School Teachers Through Training Of Frirage Massage Therapy - Rosmaneli Rosmaneli; Ali Umar; Darni Darni; Eldawati Eldawati (Jurnal Humanities Pengabdian Kepada Masyarakat, 2019)
The problem underlying this training is that the Physical Education teacher's knowledge and skills are not yet optimal in providing treatment / prevention in schools, either because of practical or sport learning activities, or in the service of UKS activities. The methods used in this training are lectures, discussions, questions and answers, demonstrations or demonstrations, methods of practice and practice. The results of the evaluation of 30 trainees were: (a) 13 people (43.33%) received an A or Excellent score, (b) 16 people (53.33%) received a B or Good rating, (c) 1 person ( 3.33%) get a C or sufficient value; and (d) the average value of achievement of training competency is 76.52 (77.64%) with a grade of B or Good.